A new synthetic derivative of cryptotanshinone KYZ3 as STAT3 inhibitor for triple-negative breast cancer therapy - Zhang, Wenda; Yu, Wenying; Cai, Guiping; Zhu, Jiawen; Zhang, Chao; Li, Shanshan; Guo, Jianpeng; Yin, Guoping; Chen, Chen; Kong, Lingyi (Cell death & disease, 2018)
Silencing STAT3 is confirmed as a promising therapeutic strategy for triple-negative breast cancer (TNBC) therapy to address the issue of its poor prognosis. In this study, the natural product cryptotanshinone was firstly remodeled and modified as a more effective STAT3 inhibitor by structure-based strategy. The synthetic derivative KYZ3 had 22-24-fold increase in antitumor activity than cryptotanshinone on two TNBC cell lines but had little effect on normal breast epithelial MCF-10A cells. Further investigation showed that KYZ3 inhibited persistent STAT3 phosphorylation. It also prevented the STAT3 protein nuclear translocation to regulate the expressions of the target oncogenes including Bax and Bcl-2. Furthermore, KYZ3 inhibited TNBC cell metastasis by decreasing the levels of MMP-9 which were directly regulated by activated STAT3. A STAT3 plasmid transfecting assay suggested that KYZ3 induced tumor cell apoptosis mainly by targeting STAT3. Finally, KYZ3 suppressed the growth of tumors resulting from subcutaneous implantation of MDA-MB-231 cells in vivo. Taken together, KYZ3 may be a promising cancer therapeutic agent for TNBC.